THE ACCOUNTING EXCHANGE. - Cotter, Arundel (The Accounting Review, 1940)
Abstract The article focuses on accounting exchange. There are many fields in which useless survivals in custom continue for an almost indefinite period; perhaps the stock illustration is found in buttons on a man's cuff, which once had a distinctly utilitarian purpose. Bookkeeping is particularly subject to instances of atavistic survival. Some of them have disappeared. One such universal custom, which even today is occasionally found in textbooks, is that of using the broad column in the conventional ledger to record the name of the contra account. In recent years, the custom of recording the contra account has very generally been abandoned except in textbooks. This in part was due to the introduction in the early 17th century of compound journal entries with the consequent meaningless entry, "Sundries," as no single account represented the amount credited. The curious fact is that while the broad column is generally left vacant there still appears as a last item the word "balance." Such an account no longer exists in American ledgers.